Elements of Manufacturing, Distribution and Logistics Quantitative Methods for Planning and Control - Thomopoulos, Nick T. (Springer International Publishing : Imprint: Springer, 2016)
This book describes a variety of quantitative methods that are vital to planning and control in the operations of the industrial world, from suppliers to manufacturing plants to distribution centers and to the dealers and stores. The topics include: forecasting, measuring forecast error, determining the order quantity, safety stock, when and how much inventory to replenish, all this for individual items and for a distribution network where the items are housed in multiple locations. Further quantitative methods are: manufacturing control, just-in-time, assembly, statistical process control, distribution network, supply chain management, transportation and reverse logistics. The methods are proven, practical and doable for most applications. The material in Elements of Manufacturing, Distribution and Logistics presents topics that people want and should know in the work place. The presentation is easy to read for students and practitioners. There is little need to delve into difficult mathematical relationships, and numerical examples are presented throughout to guide the reader on applications. Practitioners will be able to apply the methods learned to the systems in their locations, and the typical professional will want the book on their bookshelf for reference. Everyone in professional organizations like APICS, DSI and INFORMS; MBA graduates, people in industry, and students in management science, business and industrial engineering will find this book valuable.